Magnetic Cooling at a Single Molecule Level: a Spectroscopic Investigation of Isolated Molecules on a Surface. (12th April 2013) - Corradini, Valdis; Ghirri, Alberto; Candini, Andrea; Biagi, Roberto; del Pennino, Umberto; Dotti, Gianluca; Otero, Edwige; Choueikani, Fadi; Blagg, Robin J.; McInnes, Eric J. L.; Affronte, Marco
<x xml:space="preserve">Abstract</x> A sub‐monolayer distribution of isolated molecular Fe14(bta)6 nanomagnets is deposited intact on a Au(111) surface and investigated by X‐ray magnetic circular dichroism spectroscopy. The entropy variation with respect to the applied magnetic field is extracted from the magnetization curves and evidences high magnetocaloric values at the single molecule level. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>